The potential socio-political influences on kindergarten preservice teachers’ evaluations of children’s use of mathematical digital apps - Vee, Mona; Meaney, Tamsin (NOMAD Nordic Studies in Mathematics Education, 2025)
Children’s use of digital tools is mandated as a requirement in Norwegian kindergartens but is also a source of public debate. To understand how preservice teachers make sense of what could be conflicting influences of their work in kindergartens, we analyse their descriptions of using mathematical digital apps with children. After an initial analysis using the Artefact-Centric Activity Theory, the results were discussed in relationship to potential socio-political influences on the preservice teachers’ views about how digital technologies could or should contribute to providing mathematical learning opportunities. The kindergarten preservice teachers situated apps as providing the mathematical content to children, with the teacher’s role to make the app understandable to the children. The kindergarten preservice teachers’ view seemed to be affected by the curriculum and the public debate about using digital technology with young children. The results suggest a need for teacher educators to have explicit discussions about the impact of socio-political influences of digital technology with kindergarten preservice teachers.